Digital Da’i Transformation: A Training Model for Mosque Officers in Strengthening Religious Moderacy Literacy and Child Protection at Darul Hikmah Mosque, Ponorogo - Syarifan Nurjan; Asis Riat Winanto; Syamsu Arifin; Jawwad Sulthon Habiby; Fifi Arisanti; Maryono Maryono; Kasmil s Abdulwahid (MALLOMO: Journal of Community Service, 2026)
. This research aims to develop a specialized training model for mosque officers at Darul Hikmah Mosque, Ponorogo, transforming them into digital da’is capable of strengthening religious moderacy literacy and advocating for child protection. Employing a research and development method with a qualitative approach, data were collected through participatory observations, in-depth interviews with mosque administrators, and literature reviews. The data were analyzed using qualitative descriptive analysis techniques, encompassing data reduction, data presentation, and conclusion drawing. The results indicate that the digital da’i model effectively equips mosque officers with the digital literacy skills needed to produce inclusive and moderate religious content. Furthermore, the integration of child protection materials into the training curriculum ensures that the mosque serves as a safe and educational space for the younger generation. In conclusion, this transformation shifts the da'wah paradigm, where mosque officers no longer act merely as ritual caretakers but as proactive digital educators. This development ultimately fosters a more tolerant community and reinforces the mosque's role as a center of religious excellence.